2002
DOI: 10.1002/1521-3773(20020402)41:7<1229::aid-anie1229>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

The Adrenaline Test for Enzymes

Abstract: A versatile high‐throughput enzyme assay is demonstrated which is based on the colorimetric back‐titration of sodium periodate with L‐adrenaline (1). Enzyme activity is associated with the depletion of sodium periodate by the reaction product (P), and indicated by the decrease in the amount of the red dye adrenochrome (2) produced by the oxidation of adrenaline by sodium periodate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 52 publications
0
44
0
Order By: Relevance
“…Substrate profiling of the various epoxide hydrolases was done using the adrenaline test (46). Initial testing of various vicinal diols in a reaction with IO 4 Ϫ and adrenaline revealed that adenochrome was rapidly produced with all diols that are formed from the epoxides shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substrate profiling of the various epoxide hydrolases was done using the adrenaline test (46). Initial testing of various vicinal diols in a reaction with IO 4 Ϫ and adrenaline revealed that adenochrome was rapidly produced with all diols that are formed from the epoxides shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…2) or an indirect assay that measures periodate depletion by its reaction with a diol (substrates 1, 2, 4, 7, 8, 11 to 14, 16, 17, and 19 to 25). In the latter assay, the diol that is formed by epoxide hydrolase activity reacts with periodate, and the amount of remaining periodate is measured by incubating it with adrenaline to yield a colored product (46). Using these assays, it appeared that of the 12 epoxide hydrolases that were tested, 8 were active with one or more epoxides (Table 4).…”
Section: Vol 72 2006 Novel Epoxide Hydrolases From Genomic Databasementioning
confidence: 99%
“…To Scheme 1 Hydrolytic desymmetrization catalyzed by mutants of limonene epoxide hydrolase (LEH) generated by different saturation mutagenesis strategies ensure 95 % library coverage, the screening of 2912 × 3 variants of library A and 1294 × 3 variants of library B would be required. Experimentally, we assayed only 2912 and 1294, respectively, using the adrenaline on-plate pretest for activity (Wahler and Reymond 2002) followed by chiral GC analysis of the active variants.…”
Section: Residue Selection and Library Designmentioning
confidence: 99%
“…A variety of other high -throughput screening assays have been reported based on the chemoselective detection of the reaction products from untagged esters. These include fl uorogenic hydrazone formation with acetaldehyde produced by lipase/esterase -catalyzed transesterifi cation of vinyl esters in organic solvents [24] , the detection of acetic acid produced from acetate esters using an enzyme kit [25] , or the back titration of periodate with adrenaline after oxidation of the glycerol release from triglyceride hydrolysis [26,27] .…”
Section: Lipases and Esterasesmentioning
confidence: 99%
“…On the other hand various indirect assays have been reported to detect either the unreacted epoxide [46] or the carbonyl product resulting from periodate cleavage of the 1,2 -diol product [26,47,48] . These assays are suitable for fl uorescence or colorimetric assays for the hydrolysis of any epoxide of interest.…”
Section: Epoxide Hydrolasesmentioning
confidence: 99%